Analysis of English Use by Students of Industrial Engineering Study Program Unirow Tuban: Challenges And Solutions - Kalista, Anggia; Febriyanto, Devied (Indonesian EFL Journal: Journal of ELT, Linguistics, and Literature, 2023)
English Academic Purposes (EAP)is becoming increasingly important in various fields, including industrial engineering. This study aims to analyze the current challenges faced by students in the Industrial Engineering study program regarding English use and propose potential solutions. The analysis is conducted through questionnaires and interviews with students, focusing on their experiences and difficulties in English language learning. The challenges identified include limited exposure to English-speaking environments, lack of interactive learning resources, and inadequate support in English proficiency development. Purposes of this research is to address these challenges; several solutions are proposed. First, incorporating English language activities and projects into the Industrial Engineering curriculum. Second, providing more interactive learning resources, such as language labs, conversation partners, and online platforms, to enhance speaking and listening skills. Third, organizing extracurricular activities, such as English workshops. The findings of this study can guide educational institutions in identifying the challenges faced by students in English language learning and assist in the implementation of effective solutions. By improving English proficiency within the study program, they will be better prepared to thrive in a globalized industrial engineering environment.